2020
DOI: 10.3389/fsufs.2020.593053
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal Interventions for Sustainable Potato Production in Africa

Abstract: The potato (Solanum tuberosum L.) is an important tuber crop with high dietary value that could potentially help to alleviate malnutrition and hunger in Africa. However, production is expensive, with high fertilizer and pesticide demands that lead to environmental pollution, and tillage practices that negatively affect soil structure. Microorganisms of different types have increasingly been found to be useful as biofertilizers, and arbuscular mycorrhizal (AM) fungi are an important crop symbiont. AM fungi have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 152 publications
0
7
0
Order By: Relevance
“…Mycorrhiza and Azospirillum as bio-fertilizers were found to reduce nitrate and nitrite contents of potato tubers [71,72]. Mycorrhizal potato plants were reported to show improved growth and development, pathogen resistance, and productivity compared to non-inoculated potato plants [73][74][75][76][77]. Khosravifar et al [78] inoculated potato plant with Claroidoglomus etunicatum and Rhizophagus intraradices and found that R. intraradices increased tuber yield by 32.5-36.0% compared to non-inoculated control plants with a maximum root colonization percentage of 54.2%.…”
Section: Nutrient Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycorrhiza and Azospirillum as bio-fertilizers were found to reduce nitrate and nitrite contents of potato tubers [71,72]. Mycorrhizal potato plants were reported to show improved growth and development, pathogen resistance, and productivity compared to non-inoculated potato plants [73][74][75][76][77]. Khosravifar et al [78] inoculated potato plant with Claroidoglomus etunicatum and Rhizophagus intraradices and found that R. intraradices increased tuber yield by 32.5-36.0% compared to non-inoculated control plants with a maximum root colonization percentage of 54.2%.…”
Section: Nutrient Managementmentioning
confidence: 99%
“…Khosravifar et al [78] inoculated potato plant with Claroidoglomus etunicatum and Rhizophagus intraradices and found that R. intraradices increased tuber yield by 32.5-36.0% compared to non-inoculated control plants with a maximum root colonization percentage of 54.2%. Arbuscular mycorrhizal fungi are found to increase tolerance of potato plants to drought, salinity, and disease by facilitating water and nutrient acquisition and by improving overall soil structure [77].…”
Section: Nutrient Managementmentioning
confidence: 99%
“…In potato crops, inoculation with Rhizophagus irregularis and Glomus proliferum increases potato biomass, tuber ratio, tuber size and potato plant growth in low P conditions, whereas increased tuber size, which translated into increased yields over two seasons in mycorrhizal inoculated potato, was also observed 18 . Inoculation with R. irregularis and Glomus mosseae , significantly increased the average weight of tuber compared to non‐inoculated treatment, whereas in leaf and tuber an increase Zn, P and Fe concentrations was also observed 19 .…”
Section: Introductionmentioning
confidence: 96%
“…because a portion of the Rhs1A1 population may be parasitized by Trichoderma species [ 115 ]. Additionally, mycorrhiza help water and mineral absorption, and many mycorrhizal products have commercially been applied in potato production [ 126 , 127 , 128 ].…”
Section: Soil Amendment For Disease Management—from Practice To Promisementioning
confidence: 99%